The Influence Of Spirituality On The Giving Of Tithing - Kasiatin Widianto; Johannes Augustinus (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2022)
Tithing is a part of Christianity itself. Even so, the debate about the teachings of tithing among theologians is still ongoing, giving rise to two opposing camps, pros, and cons of tithing with their respective reasons. As for what is the main core of writing this research is to find out whether there is an influence of spirituality on tithing, and if there is, how much influence the spirituality of tithing. This study used a sample of 83 members of the Bethel Tabernacle Church in Surabaya who are already earning. Data collection techniques through questionnaires and analysis techniques data, namely using statistical analysis with the SPSS 19.0 program. As for the results of this study, it was found that the influence of spirituality on the tithe offering of the Congregational Bethel Tabernacle Congregation of Kalam Hidup Surabaya was included in the intense/high category. Second, the contribution of the spirituality variable in forming the tithing variable for the congregation of the Bethel Tabernacle Church of Kalam Hidup Surabaya is 36%. Third, from the resulting linear equation, it is found that if this spirituality is increased once, the development of the tithing congregation of the Bethel Tabernacle Church of Kalam Hidup Surabaya will increase by 0.588 times.